A sustainable mathematical model for design of net zero energy buildings. Issue 1 (January 2020) - Delavar, Hamed; Sahebi, Hadi
Abstract: Energy is vital recourse for economic development of today's business. The services demanded of residential and commercial buildings require substantial energy use. Energy consumption in this sector has been growing in total, gradually. As a result the high emission of greenhouse gases is released and, hence, the saving energy with better building management have made a major priority of the energy and environment sectors throughout the world. In this direction, to reduce energy consumption and mitigate environmental impacts in buildings, net-zero energy buildings (NZEB) is a very effective solution. As a result, a multi-objective model is developed to identify the best combination of materials and construction options considering their related costs, energy efficiency, and environmental impacts of buildings, simultaneously. This sustainable model is presented to construct a building considering the construction costs and energy consumption of the design options. To design the NZEB, while minimizing costs and carbon emissions, use has been made of a combination of different types of active/heating and cooling systems and renewable equipment through such high-efficiency, effective, and updated technologies as the solar panel. Finally, the case study of a residential building with two scenarios is used to demonstrate the proposed framework. The results show that, for scenarios 1 and 2 respectively using insulation thickness such as (wall, roof, and windows) and renewable equipment have the highest sustainable impact in NEBZ's performance. Abstract : Energy; Civil engineering; Energy use in building; Multidisciplinary design optimization; Renewable energy resources; Multi-objective mathematical model; Net zero energy building; Building thermal load; Sustainability